The Effect Of Employing Hologram Technology On The Achievement Motivation Off Irstinter Mediate Gradestudents (Journal of the College of Basic Education, 2024)
The study aimed to find out (the effect of hologram technology on achievement motivation among first-grade intermediate students) The research sample consisted of (58) female students of the first intermediate grade, for the second semester of the academic year (2023-2024 AD), Noor Al-Islam Intermediate School of the General Directorate of Education of Baghdad Governorate / Rusafa I was chosen intentionally, and by random selection, Division (D) was chosen to be the experimental group that was studied according to hologram technology by (30) students, and Division (C) to be the group The control that studied according to the usual method by (28) students, and the two groups were divided into variables (intelligence, chronological age, previous information in mathematics, previous achievement in mathematics, and the educational level of the parents). The achievement motivation scale prepared by (Othman, 2004) was adopted, which includes (24) items, the honesty and stability of the scale was extracted if the stability coefficient reached (0.68) The experiment was applied in the second semester of the academic year (2023_2024) and after the completion of the experiment, the achievement motivation scale was applied to the two research groups and after collecting data and using appropriate statistical means, the results showed a statistically significant difference between the experimental and control groups in the achievement motivation scale and in favor of the experimental group, and in light of the results of The research recommended the use of hologram technology for all academic levels as it raises the level of achievement motivation, as well as holding training courses for mathematics teachers and during service on hologram technology and how to employ it in teaching mathematics